Breast self-examination among older women in Ireland: The Irish Longitudinal Study on Ageing -TILDA. (20th October 2021) - Bhardwaj, N; Fitzpatrick, P
Abstract: Background: Regular breast self-examination (BSE) is a simple, cost-effective way of early breast cancer detection, particularly for women outside eligible screening age and for interval cancers. Although mammographic screening is the current most effective breast screening tool, the importance of regular BSE and breast awareness may be overlooked. The study aimed to identify socio-demographic, lifestyle and health-related factors associated with BSE practice among women in Ireland. Methods: This study was conducted using Wave 4 data from The Irish Longitudinal Study on Ageing (TILDA), which collects health-related information from people aged 50 plus in biennial data collection waves. Those women aged 50-64 (eligible breast screening age in 2016) were selected. Following univariate analysis, logistic regression analysis was performed on selected variables to determine the factors independently associated with BSE practice. Results: The prevalence of BSE was 70.7%. There was no significant association found between socio-demographic, lifestyle or health related factors and BSE. On logistic regression analysis, family history of cancer was not found to be associated with increased practice of BSE (Adjusted Odds Ratio (OR) 1.02, 95% Confidence Interval (CI) 0.79-1.31, p = 0.86). Having attended for mammogram showed a non-significant reduction in the likelihood of doing BSE (Adjusted OR 0.77, 95% CI 0.58-1.02, p = 0.07). Conclusions: There are few studies on BSE from developed countries and this is the first from Ireland. BSE prevalence was 61%, 22.6% and 46.8% from Canada, United Kingdom and United States respectively, and was considerably lower from Asian and African countries. Women in this study were more educated than the general population counterparts, this might have overestimated BSE prevalence and obscured true associations. While we did not identify significant associations there is a suggestion that attending for mammography reduces women's interest in BSE. Key messages: Being 'Breast Aware' and BSE are important alongside mammography for early detection of breast cancer. In countries where screening mammography is unavailable, BSE is an important detection tool.